DESAIN PEMBANGKIT LISTRIK TENAGA SURYA - Marfizal, Marfizal; Tonadi Shodiq, Een; Wardianto, Dedi; Sufiyanto, Sufiyanto (Jurnal Teknologi dan Vokasi, 2024)
The distribution of PLN electricity to remote areas has not been achieved so there are other alternative resources needed, for example solar power plants. The aim of this research is to design and analyze the potential for a solar power plant with an off-grid system that can be used to supply residential homes when PLN power goes out. This solar power plant is designed for a load of 17 kwh / per day, the efficiency (ηinv) of the inverter is 93%, the efficiency of the battery block is ηBAh = 85%, the DC system voltage is chosen as 48 V. The solar power generation system designed in this research is an off system -lattice. The main components were chosen based on the calculation results for the number of panels of 3563 Wp, with a total storage battery of 1172 Ah. If you use 48v/160ah Lithium batteries connected in parallel using 7 batteries with a charging time of 7.3 hours, minimum scc current of 74 Ah, inverter current of 41.6 Ah with a panel tilt angle of 15 degrees.